Influence of platelet rich plasma on osseointegration in controlled diabetic patients - Aaqil, Malik (2008)
Success rates of dental implants in controlled diabetics is less than normal patients and considering the large number of diabetic patients a solution and improvement is needed. Diabetic patients are known to have delayed bone and wound healing compared to normal patients. The objective of this study was to improve success rates by employing a minimally invasive implant to decrease the size of the wound and autogenous platelet rich plasma (PRP) to enhance the bone healing. This was a Non-randomized clinical trial employing a splitmouth design consisting of patients selected from the diabetic clinic at the Hospital University Sains Malaysia. Using a one-stage surgical protocol, a total of 28 Mini Drive Lock implants (Intra-lock® USA) implants with lengths of 10, 11.5, 13 and a diameter of 2.0 mm of 2.5 mm were inserted in edentulous and partially edentulous patients. Patients included as controlled diabetic had HbA1c = 7 or less, FBS = 7 mmoi/L or less, RBS = 10 mmoi/L or less. Total sample size was 14 patients, each patient received two implants (n=28 implants, 14 = trial & 14 = control), where one implant (without PRP) is placed, and another implant (with PRP) is placed on the contra lateral side of the same jaw. Implants were placed in the maxilla or the mandible in each patient. Results of 14 test and 14 control implants is reported. Radiographic density evaluation was done at 3, 6 and 9 weeks after placement. Measurements were done at five points around the implants using histogram and densitometry with the VIXWIN xvii 2000 Ver. 1.8 software. A total of 28 implants were placed, 1 implant did not attain primary stability at placement due to lack of bone width and was removed, it was not considered failure to integrate. At 9 weeks all 27 mini implants placed showed osseointegration on radiographs. Statistically, results showed no significant difference between radiographic density of the two groups (P=0.125) during the time period of the study, however mini implants were successfully followed up at 9 weeks. This study showed no significant difference of wound healing when comparing groups of PRP and non-PRP in controlled diabetic patients. However both groups have shown good osseointegration radiographically and the stability of implants was still maintained over the period of nine weeks although with immediate loading. The use of minimally invasive implant procedure can help to improve the soft tissue wound healing and bone osseointegration in diabetic patients with or without PRP. In conclusion the wound healing in diabetic patients is highly dependant upon the severity of tissue trauma, therefore emphases on implant placement technique should be considered.